2010
DOI: 10.1089/vbz.2009.0034
|View full text |Cite
|
Sign up to set email alerts
|

Brucella canisCausing Infection in an HIV-Infected Patient

Abstract: From the blood culture of an HIV-positive patient with a febrile syndrome (CD4 count 385 cells/microL and viral load nondetectable), Brucella canis was isolated. The patient was presumptively infected from his dogs, which tested positive, and showed good outcome after the therapy with doxycycline-ciprofloxacin, and the HIV infection would seem not to have been influenced by brucellosis. To our knowledge, no other case of B. canis in the setting of HIV infection has been reported in the literature, and the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 8 publications
0
26
0
4
Order By: Relevance
“…However, clinical signs did not develop in four adults in the same household, all of whom had been exposed to the puppy (Dentinger et al, ). Several recent reports have suggested that B. canis in HIV‐infected patients highlights the high risk within this population (Lucero, Maldonado, et al, ; Moreno et al, ). Our conclusion is consistent with aetiological characteristics of B. canis in China .…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical signs did not develop in four adults in the same household, all of whom had been exposed to the puppy (Dentinger et al, ). Several recent reports have suggested that B. canis in HIV‐infected patients highlights the high risk within this population (Lucero, Maldonado, et al, ; Moreno et al, ). Our conclusion is consistent with aetiological characteristics of B. canis in China .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent cross-sectional seroprevalence studies in Iran have shown an association between HIV and brucellosis seroprevalence. 56,57 Case reports have proposed an association between HIV and B. canis, 58,59 and between HIV and relapsing brucellosis. 60 Consistent with our study, others have found no association between HIV and brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent poor association between HIV and brucellosis and that the impression that HIV infection does not seem to increase the incidence of brucellosis, several cases as well as case series on the development of brucellosis in HIV infected individuals have been reported [86,[160][161][162][163][164][165][166]. The risk factors for Brucella infection in HIV patients are male sex and intravenous drug abuse [162,163].…”
Section: Brucellosis In Patients With Hiv Infectionmentioning
confidence: 99%